The Role of the Supplier on the Performance of New Product Development through the Quality of the Team - Yulasmi, Yulasmi; Syafwandi, Syafwandi; Ridwan, Muhammad (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
This study tries to explain the influence of the supplier's role on the performance of the new product development team through the quality of the team moderated by the influence of corporate culture. The object of observation is the New Product Development Team (part of the company's R&D Division, Maspion Ltd. Corp. (Tbk),  Sidoarjo. Objectives:  Analyze the effects of the supplier's role on the performance of the new product development team, the supplier's role on the quality of the new product development team, and how corporate culture strengthens the influence of the supplier's role on the quality of the new product development team.Methodology: Observations were made on 78 employees of the New Product Development Team at the R&D Division of Maspion Ltd. Corp. (Tbk) Units I, II, III, in Sidoarjo, and Unit IV in Surabaya. The analytical method used is the structural equation modelFindings:  (1) the role of the main supplier is important because it has a significant positive effect on the quality of the team in the innovative process; (2) the quality of the team has a significant positive effect on the performance of the new product development team; and (3) corporate culture strengthens the influence of the supplier's role on team quality.  Conclusion: Corporate culture and the role of suppliers are able to improve the quality of the new product development team and the team's performance in producing new products or product lines that are more marketable.